Extraction of Fickian water diffusion in polymers using terahertz time-domain spectroscopy. (4th October 2022) - Engelbrecht, Sebastian; Pichot, Vincent; Goepfert, Thomas; Lin, Hungyen; Fischer, Bernd M.
Abstract: The dynamic behavior of polycarbonate and poly(methyl methacrylate) upon water immersion at temperatures of 40 °C and 70 °C was studied by gravimetric measurements and by terahertz time-domain spectroscopy. Time-resolved measurements of the terahertz refractive index and absorption coefficient show a good agreement to the gravimetric measurements. Assuming a Fickian diffusion mechanic the diffusion coefficients were extracted from both methods. It was found that the terahertz measurements provide a reliable non-contact way to study the water diffusion in polymers. Especially, the THz absorption coefficient seems to be a robust method to determine the diffusion coefficients. Highlights: Extraction of Fickian diffusion constants in polymers by THz time domain spectroscopy. Terahertz optical constants are in good agreement against gravimetric analysis. A contactless technique to investigate water mobility in polymers.